Prevalence and Imaging Characteristics of Nonmyelopathic and Myelopathic Spondylotic Cervical Cord Compression - Kovalova, Ivana; Kerkovsky, Milos; Kadanka, Zdenek; Kadanka, Zdenek; Nemec, Martin; Jurova, Barbora; Dusek, Ladislav; Jarkovsky, Jiri; Bednarik, Josef (Spine, 2016)
STUDY DESIGN: Cross-sectional population-based observational study. OBJECTIVE: To estimate the prevalence of nonmyelopathic spondylotic cervical cord compression (NMSCCC) and cervical spondylotic myelopathy (CSM) in a population older than 40 years and to evaluate the magnetic resonance imaging (MRI) characteristics of these conditions. SUMMARY OF BACKGROUND DATA: The prevalence of neither NMSCCC nor CSM is known and there exists no commonly accepted quantitative MRI definition of cervical cord compression. METHODS: A group of 183 randomly recruited volunteers, 93 women, median age 66 years, range 40-80 years, underwent MRI examination of the cervical spine and spinal cord on a 1.5 T device using conventional sequences from disc levels C2/C3 to C6/C7. The imaging criterion for cervical cord compression was defined as a change in spinal cord contour at the level of an intervertebral disc on axial or sagittal MRI scan. RESULTS: MRI signs of cervical cord compression were found in 108 individuals (59.0%; 95% CI: 51.5%-66.2%); their numbers increased with age from 31.6% in the fifth decade to 66.8% in the eighth. Clinical signs of symptomatic CSM were found in two cases (1.1%), and 75 cases (41.0%) were without compression. An anteroposterior cervical canal diameter at the level of intervertebral disc (CDdisc) of less than 9.9 mm was associated with the highest probability of NMSCCC-odds ratio (OR) = 32.5, followed by a compression ratio of ≤0.5: OR = 11.1. CONCLUSION: The prevalence of NMSCCC in a population older than 40 years is higher than previously reported and increases with age. CDdisc and compression ratio had the highest capacity to discriminate between subjects with and without asymptomatic compression, and their cut-off values could be used to objectify criteria for cervical cord compression. LEVEL OF EVIDENCE: 2.
Keywords: senioři; páteřní kanál; komprese míchy; Cross-Sectional Studies; Prevalence; senioři nad 80 let; krční mícha; Middle Aged; mužské pohlaví; prevalence; Spondylosis; průřezové studie; Adult; Spinal Cord Compression; Cervical Cord; magnetická rezonanční tomografie; Aged, 80 and over; Magnetic Resonance Imaging; ženské pohlaví; spondylóza; Humans; lidé středního věku; Spinal Canal; krční obratle; dospělí; Female; Aged; Cervical Vertebrae; lidé; Male